Influence of plot size on distribution analyses and effects of altitude on spatial patterns of palm heart in Submontane Tropical Rainforest, Ibirama, Brazil - Pereira, Lílian Daniel; Schröder, Thomas; Chies, Juliane; Zanchetti, Flávio; Dimas Fleig, Frederico (Bosque (Valdivia), 2017)
The knowledge about the behavior of the species and its analysis is very important in order to support management and conservation techniques. Therefore, the aims of this study were to analyze spatial distribution of palm heart (Euterpe edulis) and verify the influence of altitude on spatial distribution. The spatial distribution was calculated with the indexes of Payandeh, Hazen and Morisita. To assess the influence of altitude on spatial distribution, we calculated Kolmogorov-Smirnov test of complete spatial randomness with altitude as covariate and we also calculated an estimate of the intensity as a function of altitude. The study was developed in a seed collection area in Floresta Nacional (FLONA) in Ibirama, Santa Catarina. Sampling consisted of five ten-meter-wide strips. False coordinates of E. edulis with more than 10 cm of diameter at breast height were recorded. Euterpe edulis showed spatial clustered distribution in all plot sizes and all indexes used. Morisita was the best index for describing spatial distribution. The occurrence of E. edulis was higher in intermediate altitude. Therefore, it is recommended to take into consideration the existence of clusters and of altitude influence in order to promote management and conservation of this species.